EXPLORING THE EFFECTIVENESS OF CHATGPT AS A CONVERSATIONAL PARTNER ON EFL STUDENT’S SPEAKING SKILLS: A QUASI-EXPERIMENTAL STUDY IN INDONESIA HIGHER EDUCATION - Maharani, Zalfa Cabrina; Siagiyanto, Bambang Eko; Refai, Refai (Universitas Muhammadiyah Metro, 2025)
This study explores the effectiveness of ChatGPT in enhancing the speaking skills of EFL undergraduate students in the Hospital Administration program at Universitas Muhammadiyah Metro. A quasi-experimental research design was employed, involving 42 first-semester students divided into two groups: 21 students in ARS 1 as the experimental group and 21 students in ARS 2 as the control group. The experimental group received treatment using specific prompts designed to initiate conversations with ChatGPT. Data were collected through oral tests conducted before and after the intervention (pre-test and post-test). The results indicate a statistically significant improvement in the speaking skills of students in the experimental group. Hypothesis testing showed a significant value of <0.000 for the first hypothesis and 0.004 for the second, both below the threshold of 0.05, indicating that the alternative hypotheses were accepted. In conclusion, the use of ChatGPT had a positive and significant effect on improving the speaking skills of EFL students in the Hospital Administration program. The results highlight the potential of ChatGPT to supplement classroom speaking activities, while contributing to research on AI in EFL learning.